The implications of UBI on the utility function and tax revenue: Further calibrating of basic income effects - Bernhard Neumärker; Jette Weinel (University of Freiburg, Institute for Economic Research, Department of Economic Policy and Constitutional Economic Theory, 2024)
Economic modeling of Universal Basic Income (UBI) often fails to consider how individuals' utility calculations shift with unconditional transfers. In this paper we further develop the model of our previous paper - The Implications of UBI on Utility Functions and Tax Revenue (Neumärker, B., Weinel, J., 2022). We contend that, while traditional fiscal models rely on an additively separable relationship between consumption and labor, the utility calculation for individuals influenced by UBI is better represented by a multiplicative relationship. This shift arises from the time sovereignty afforded by UBI, empowering individuals to become selfdetermined, creative, and intrinsically motivated. We explore the implications of the UBIadapted utility function on tax revenue. Specifically, we analyze the consumption tax revenue curve under UBI (multiplicative preferences) versus a means-tested welfare system (additive separable preferences).
Keywords: 330; Basic Income; Laffer Curve; Utility Function; Consumption Tax; Time sovereignty; Intrinsic Motivation